Remoção do agente hormonalmente ativo etinilestradiol por pré-oxidação e coagulação: estudo em escala de bancada - Fabio Jose Bianchetti (2008)
Endocrine disrupting compounds (EDC) are a particular group of organic contaminants that have been hightlighted due to their potential adverse effect towards nervous, endocrine and immune systems of wildlife and humans. Their presence in drinking water and food has beenpostulated to cause increase in human diseases such as cancer; growth and neurological deficiencies; fertility and glands disfunctions; among others. It has already been shown such adverse effects in wildlife such as fish, frogs, birds and mammals. One of the most relevant EDCs is the 17-ethinylestradiol, a synthetic hormone used in contraceptive pills andhormonal replacement therapies. This work evaluated the removal of 17-ethinylestradiol (ethinylestradiol stock solutions were prepared with the pure compound and contraceptive pills and then properly diluted to prepare working solutions containing 1 or 7 mg.L-1, respectively) spiked in synthetic water (10,0 0,5 uT e 100 5 uT) during bench scale water treatment consisting of the following processes: i) conventional water treatment, without filtration and disinfection, using alum and ferricchloride as coagulants; ii) pre-oxidation with sodium hypochlorite. A total of 152 samples were collected from these studies in which the 17-ethinylestradiol was analysed by liquid chromatography coupled to mass spectrometry (LC-MS). For both coagulants and turbidity values, the settling unit did not seem to significantly remove 17-ethinylestradiol. On the other hand, the pre-oxidation resulted in an efficient removal of17-ethinylestradiol since under usual operational conditions (sodium hypochlorite concentration of 1 or 3 mg.L-1 and contact time of 5, 30 or 60 min), the removal efficiencies varied from 40,9 to 99,2%. As observed for the settling unit, turbidity did not seem do interfere in the oxidation and removal of 17-ethinylestradiol.